Service users' experiences of an early intervention in psychosis service: an interpretative phenomenological analysis - Harris, Katy (2010)
Objectives: Previous research regarding Early Intervention in Psychosis (EIP) has mainly adopted quantitative methodologies, in order to study the effectiveness of EIP services. Research studies which have explored service-users’ experiences of EIP services are small in number. This research aimed to explore service-users’ experiences of being in contact with an EIP service, its impact of their experience of psychosis and current life situation. Design: Interpretative Phenomenological Analysis (IPA) was used to conduct an in-depth qualitative study of a small sample of EIP service-users, in order to explore their experiences of being in contact with the service.